Widening student access and participation in Allied Health Sciences: A critical reflection - Ige, B.O.; Amosun, S.L.; Hartman, N. (South African Journal of Higher Education, 2017)
ABSTRACT Widening of access and participation has become a paramount agenda for Allied Health Sciences education in South Africa. In response to the need the Department of Health and Rehabilitation Sciences, Faculty of Health Sciences, University of Cape Town introduced the Intervention Programme (IP) in 2009 as a strategy for widening of access and participation student. This study reflects on the design and implementation of IP, the complexities of the diversity of students entering the IP, and the implications for curriculum restructuring in the first year of study and beyond. The authors drew on Mezirow’s (1990) theory of transformative learning to explain the multifaceted challenges encountered through our own reflection as programme designers and facilitators, as well as organisers of and participants in curricular reviews using data from student interviews, student performance in first and subsequent years of study, and review documentation. The study shows that curriculum restructuring for a diversifying student body across multiple programmes is a complex process with interrelated and influential factors. Our critical reflections revealed the complexities of aligning intentions that are significantly flawed by presuppositions relating needs and outcomes.